Urgensi Perda Penanggulangan Wabah Menular di Kota Yogyakarta: The Urgency of Local Regulations for Overcoming Infectious Outbreaks in Yogyakarta City - As-Shidiq, Abdullah Widy; Reza, M. Hilmi Miftahzen; Wafi, Muhammad Syafiq (Fakultas Hukum Universitas Negeri Semarang, 2021)
The research on